2004
DOI: 10.1111/j.1525-1594.2004.00020.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Chitosan Scaffold Containing TGF‐β1 Encapsulated Chitosan Microspheres on In Vitro Chondrocyte Culture

Abstract: The objectives of this study were (1) to develop a three-dimensional chitosan scaffold in combination with transforming growth factor-beta1 (TGF-beta1)-loaded chitosan microspheres and (2) to evaluate the effect of the TGF-beta1 release on the chondrogenic potential of rabbit chondrocytes in the scaffolds. TGF-beta1 was loaded into chitosan microspheres using an emulsion-crosslinking method, resulting in spherical shapes with a size ranging from 0.3 to 1.5 microm. Controlled release of TGF-beta1, as measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(40 citation statements)
references
References 36 publications
2
35
0
1
Order By: Relevance
“…The type II collagen was assessed according an immunohistochemical method described elsewhere [41]. The scaffolds were first fixed with 4% formaldehyde-buffered saline (pH 7.4), washed in 70% ethanol, dehydrated in ethanol at sequential concentrations, and then embedded in paraffin.…”
Section: Glycosaminoglycan and Collagen Testmentioning
confidence: 99%
“…The type II collagen was assessed according an immunohistochemical method described elsewhere [41]. The scaffolds were first fixed with 4% formaldehyde-buffered saline (pH 7.4), washed in 70% ethanol, dehydrated in ethanol at sequential concentrations, and then embedded in paraffin.…”
Section: Glycosaminoglycan and Collagen Testmentioning
confidence: 99%
“…However, it remains to be determined to what extent the cells contributed to the clinical improvement, and current challenges point to the control of the differentiation and proliferation processes of stem cells once they have been implanted into patients t59). polymeric scaffolds and cultured in a medium enriched with Transforming Growth Factor-~(TGF-) and ascorbic acid (56). In the dental field, a study by Yamada et al investigated the possibility of a rapid and more effective bone regeneration around dental implants using an injectable tissue-engineered bone with MSCs and platelet-rich plasma (57).…”
Section: Current Application and Future Directions Of Mscs Therapymentioning
confidence: 99%
“…Polysaccharide microspheres have been explored for the controlled release of growth factors within three-dimensional tissue engineering scaffolds, to augment cellular proliferation and extracellular matrix formation. Lee et al (2004a) presented results suggesting that transforming growth factor (TGF-b1) which controls cell proliferation, and differentiation loaded into chitosan microspheres then incorporated into cell scaffolds seeded with chondrocytes, have the potential to enhance cartilage formation. In another study vascular endothelial growth factor (VEGF), essential for angiogenesis, has shown high encapsulation efficiency in alginate microspheres followed by sustained zero-order release by diffusion over 3 weeks (Elcin et al, 2001).…”
Section: The Development Of Biopharmaceuticalsmentioning
confidence: 92%